CODE MIXING USED BY RADIO BROADCASTER OF PESONA FM ON RADIO PROGRAM OF SONG REQUEST - Adelia Rezki Kasoema; Zul Amri (English Language and Literature, 2016)
This paper is aimed to: (1) identify the types of code mixing used by radio broadcasters of Pesona FM radio program of song requests; (2) determine the functions of code mixing used by the radio broadcaster in the radio program. The data in this paper are all words, phrases, and clauses or sentences that belong to the code mixing. Data sources are obtained from recording of conversation between the radio broadcasters and listeners in the radio program. The method used in this paper is descriptive. Data was analyzed using the theory advanced by McKay and Nancy (1996: 58-60) for classifying the types of code mixing such as inserting of word, inserting of phrases, and inserting of a clause or sentence. The theory also used to classify the functions of code mixing such as identity marking, strategy of neutrality, stylistic function, and socio-expressive function. From a total of 82 data, the researchers found 44 data (53.65%) belongs to the inserting of word, the 26 data (31.70%) belong to the inserting of phrases and 12 data (14.63%) belongs to the inserting of a clause or sentence. The inserting of word is the most dominant type of code mixing used and the inserting of a clause or sentence is the least. Furthermore, from the 82 data, the researchers also discovered the function of code mixing and found 8 data (9.75%) were included into the identity marking, 4 data (4.87%) were included into the strategy of neutrality, 53 of data (64.63%) belongs to the stylistic function, and 17 data (20.73%) belongs to the socio-expressive function. In the function of the code mixing, the stylistic function is the most dominant function used, while the identity marking is the least.CODE MIXING USED BY RADIO BROADCASTER OF PESONA FMON RADIO PROGRAM OF SONG REQUEST